Assessing and genotyping threatened staghorn coral Acropora cervicornis nurseries during restoration in southeast Dominican Republic - Johanna Calle-Triviño; Renata Rivera-Madrid; María Geovana León-Pech; Camilo Cortés-Useche; Rita Inés Sellares-Blasco; Margarita Aguilar-Espinosa; Jesús Ernesto Arias-González (PeerJ, 2020)
Acropora cervicornis is a structurally and functionally important Caribbean coral species. Since the 1980s, it has suffered drastic population losses with no signs of recovery and has been classified as a critically endangered species. Its rapid growth rate makes it an excellent candidate for coral restoration programs. In 2011, the Fundación Dominicana de Estudios Marinos (Dominican Marine Studies Foundation, FUNDEMAR) began an A. cervicornis restoration program in Bayahibe, southeast Dominican Republic. In this study, we present the methodology and results of this program from its conception through 2017, a preliminary analysis of the strong 2016 and 2017 cyclonic seasons in the greater Caribbean, and a genetic characterization of the “main nursery”. The mean survival of the fragments over 12 months was 87.45 ± 4.85% and the mean productivity was 4.01 ± 1.88 cm year−1 for the eight nurseries. The mean survival of six outplanted sites over 12 months was 71.55 ± 10.4%, and the mean productivity was 3.03 ± 1.30 cm year−1. The most common cause of mortality during the first 12 months, in both nurseries and outplanted sites, was predation by the fireworm, Hermodice carunculata. We identified 32 multilocus genotypes from 145 total analyzed individuals. The results and techniques described here will aid in the development of current and future nursery and outplanted site restoration programs.